CONTROL OF UPPER LIMB REHABILITATION DEVICES: A BIBLIOMETRIC STUDY - Norsinnira Zainul Azlan; Ibrahim Hafizu Hassan, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The study analyzes research trends, collaboration patterns, and key focus areas in the field of upper limb rehabilitation devices using bibliometric methods. With advancements in robotics and assistive technologies, these devices have become crucial for individuals with upper limb impairments, particularly stroke survivors. However, the rapid increase in publications necessitates a comprehensive understanding of research directions and influential contributions. This study used the Scopus Analyzer and VOSviewer software to examine a dataset of 1,208 publications. The Scopus analyzer provided insights into publication trends and author productivity. At the same time, VOSviewer was employed to map keyword occurrences and co-authorship networks, revealing the main topics and collaborative linkages across countries. The analysis highlights a steady increase in research output from 2015 to 2024, with a slight decline in the last two years, likely due to shifting research priorities or market saturation. Keywords such as "rehabilitation," "stroke," "upper limb," and "exoskeleton" indicate strong interest in assistive technology for motor recovery, while terms like "adaptive control" and "impedance control" emphasize the importance of control mechanisms tailored to patient needs. Additionally, international collaboration networks are led by countries like China, the United States, and Italy, reflecting their high research impact and extensive partnerships. In conclusion, this bibliometric analysis offers valuable insights into the progress and collaborative efforts within upper limb rehabilitation devices research, highlighting the interdisciplinary nature of the field and identifying potential areas for future exploration. This study serves as a reference for researchers aiming to develop further rehabilitation control solutions that enhance the quality of life for patients with upper limb impairments.